Ageing with a twist: Intimacy and care amongst LGB older adults in Portugal - Santos, A. C. (2022)
Ageing is increasingly at the centre of both local and international politics and policies. However, the attention on the intersection of ageing and sexual diversity has remained largely absent from research agendas in the Portuguese context. This article addresses issues of care and intimacy experienced by self-identified lesbian, gay and bisexual (LGB) people over the age of 60 both before and during the COVID-19 outbreak in Portugal. The article is divided into four sections. In the introduction, the main issue addressed will be an explanation that draws on a theoretical framework informed by both LGBTQI+ and ageing and life course studies. The second section gives a necessarily brief overview of the socio-legal context of LGBTQI+ issues in Portugal and provides information regarding methodological aspects of the research. The third section explores experiences, prior and during the pandemic, of older adults who self-identify as LGB in the Portuguese context. Accompanied by excerpts from interviews originally carried out in 2019 and 2020, this section is structured around three topics: pandemic 2.0.; isolation and relational loneliness and health and care networks. The last section discusses the current impact of ageing and of ageism on older LGB adults, while also offering recommendations for future policy and scholarly work.